Alternatives to Liberal Democracies and Their Consolidation in Central and Eastern Europe - Radoslaw Markowski; Michał Kotnarowski (Politics and Governance, 2025)
This article tentatively examines the rise and impact of populism, illiberalism, and authoritarianism as alternatives to liberal democracy in Central and Eastern Europe, using data from the 10th European Social Survey. It focuses on the complex relationship between ideologies and political regimes, where citizens’ attitudes act as mediating factors. The task of categorizing anti‐liberal and non‐democratic regimes is ontologically distinct from analyzing and understanding the essence of anti‐liberal or non‐democratic ideas. Nevertheless, a comprehensive understanding of either aspect requires an appreciation of both. Former studies show no strict determinism between regime type and public ideology, though some alignment is usually present. Our findings reveal that populist and illiberal views often reduce political legitimacy, whereas authoritarian attitudes can enhance it. These findings indicate a complex interrelationship between public attitudes, political ideologies, and regimes with political legitimacy, particularly in contexts marked by democratic regression and ascendant authoritarian inclinations. This nuanced interplay suggests divergent paths in democratic evolution across Central and Eastern European regions, with some countries moving toward stable illiberal regimes, while others face contested political climates.